STUDY ON OPTIMIZING SPRAYING DISTANCE AND FLOWRATE GAS RATIO PARAMETERS FOR COATING METCO 405A USING FLAME SPRAY METHOD FOR DART-7 ENGINE APPLICATIONS - Ramadhan, Nugraha
Thermal spray is a coating method that involves spraying coating materials in the form of molten droplets, semi-molten, or solid particles onto a substrate surface at high deposition rates. One commonly used thermal spray technique in the industry is flame spray, due to its ease of use, low cost, and the wide range of applicable coating materials and substrates. In this method, several operational parameters control the microstructure and mechanical properties of the resulting coating, including the fuel-to-oxygen flow rate ratio and the spraying distance of the coating material. An application of flame spray is in the aerospace industry, specifically for coating in the repair process of diffuser vane rings. This study uses Metco 405A (Ni-20wt% Al) as the coating material, AISI 321 as the substrate, and acetylene as the fuel. The experiments and testing were conducted at the Bandung Institute of Technology and PT Nusantara Turbin dan Propulsi. A series of coating parameter variations were conducted to investigate the effects of the fuel-to-oxygen flow rate ratio and spraying distance on the microstructure and mechanical properties of the resulting coating. The microstructure and mechanical properties of the coating were examined at acetylene-to-oxygen gas flow rate ratios of 1:1, 1:1,5, and 1:1,8, and at spraying distances of 4, 6, and 8 inches for each gas flow rate variation. The microstructure was analyzed using SEM-EDS, while the mechanical properties were evaluated through HRC hardness tests and peeling-off tests to assess coating strength. Based on the characterization and testing results, the effects and optimal parameters of the acetylene-to-oxygen gas flow rate ratio and spraying distance on the microstructure and mechanical properties of the coating will be determined. Increasing the spraying distance leads to a rise in the oxide percentage and a decrease in the porosity percentage for each variation of the acetylene-to-oxygen gas flow rate ratio. The oxide percentage and porosity for each variation indicate the influence of the gas flow rate ratio on the mechanical properties of the coating. The lowest oxide percentage value was achieved at an O/A ratio of 1 with a 4-inch distance, at 8.08%. The lowest porosity percentage value was also achieved at an O/A ratio of 1,5 with a 8-inch distance, at 2.77%. The highest coating strength was achieved with a gas flow rate ratio of O/A 1,8, with the peak value of 49,65 MPa obtained at a spraying distance of 8 inches. The highest coating hardness was found with a gas flow rate ratio of O/A 1,5, with the peak value of 25,9 HRC also achieved at a spraying distance of 8 inches. The optimal parameters for the best microstructure and mechanical properties were found to be a gas flow rate ratio of 1:1,8 with a spraying distance of 8 inches.